2021
DOI: 10.3390/ijerph18105209
|View full text |Cite
|
Sign up to set email alerts
|

The Male Experience of Suicide Attempts and Recovery: An Interpretative Phenomenological Analysis

Abstract: Suicidal behaviour is a complex phenomenon—its aetiology spans biological, psychological, environmental, social and cultural facets. Men’s deaths by suicide outnumber women in every country in the world. This study explored the male experience of suicide attempts and recovery as well as factors which may be protective for men. Men (n = 12) participated in semi-structured face-to-face interviews which were subjected to Interpretative Phenomenological Analysis (IPA). Four master themes were identified: (1) “char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Operating in the low-level-identification modus might prevent a person from experiencing inconsistency in relation to higher-order goal conflicts (e.g., the goal of killing oneself might conflict with the goal of watching one’s children grow up and protecting them from emotional trouble) and thus might contribute to suicidal behavior being executed without interferences. This change in thinking is also demonstrated in a qualitative study with men who survived a suicide attempt ( 42 ).…”
Section: New Directions Of Conceptualizing Suicidality: the Dual-syst...mentioning
confidence: 70%
“…Operating in the low-level-identification modus might prevent a person from experiencing inconsistency in relation to higher-order goal conflicts (e.g., the goal of killing oneself might conflict with the goal of watching one’s children grow up and protecting them from emotional trouble) and thus might contribute to suicidal behavior being executed without interferences. This change in thinking is also demonstrated in a qualitative study with men who survived a suicide attempt ( 42 ).…”
Section: New Directions Of Conceptualizing Suicidality: the Dual-syst...mentioning
confidence: 70%
“…Harris et al ( 58 ) reported that talking to people and performing daily activities that demanded a level of concentration (e.g., exercising, listening to music, cooking, and playing computer games) were helpful for patients with schizophrenia diagnoses to suppress their suicidal ideation. Several other research also concluded that emotional expression through talking or writing played an essential role in a suicidal recovery process ( 29 , 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…It may be adversity such as the coming-out process, stressful life events, combat distress, posttraumatic stress symptoms linked to sexual assault or childhood abuse, being in late life, depressive symptoms, and a diagnosis of schizophrenia ( 28 , 34 , 42 , 44 , 50 , 64 , 66 , 67 ). This adversity also includes events directly relating to suicide, which are the strongest predictors of future suicide, such as suicide ideation or suicide attempt ( 71 , 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors with the strongest evidence in men were alcohol and/or drug use/substance use disorder [12,13], being unmarried, single, divorced, or widowed [14,15], and a current diagnosis of depression [16]. To better understand suicidal behavior and ideation in men, some studies also examine the role and influence of gender norms, traditional gender role perceptions and problem-solving strategies [17][18][19]. In addition, it is often discussed that men show less help-seeking behavior in case of mental disorders than women.…”
Section: Introductionmentioning
confidence: 99%